Eksistensi Patron Klien dalam Pencapaian SDGs Desa Bulango Raya Kecamatan Tomilito Kabupaten Gorontalo Utara - Juriko Abdussamad (Univeristas Negeri Gorontalo, 2022)
The Sustainable Development Goals (SDGs) were declared on September 25, 2015 at the United Nations Headquarters in New York by 193 countries as a commitment to the Global Development Agenda. The sustainable development goals are a continuation and refinement of the Millennium Development Goals (MDGs) which have been implemented during the 2000-2015 period. The SDGs are an improvement from the previous Global Development Agenda, because development commitments do not only focus on human development, but also environmentally friendly economic development and environmental development. The SDGs place humans as central actors and connoisseurs of development outcomes aimed at human well-being. Whether development will produce the well-being that humans want depends on the behavior of humans themselves towards nature and its use for the purpose of welfare today and for future generations (Patron-Client relationship). Patron-client relationship is the exchange of relations between the two roles which can be expressed as a special case of bond involving instrumental friendship in which an individual with a higher socio-economic status (patron) uses his influence and resources to ...Departing from this problem, the solution that will be offered in this community service is that together with the community will carry out KKNT Village Development services in the form of giving the role of traditional leaders, religious leaders and community leaders (Client Patrons) in achieving SDGs in Bulango Raya Village, Tomilito District. North Gorontalo Regency.